475 Local Conditional Induction of Brain Arteriovenous Malformations in Alk1-Inducible Knock-Out Mice. (April 2023) - Scherschinski, Lea; Han, Chul; Winkler, Ethan A.; Vajkoczy, Peter; Lawton, Michael T.; Oh, S. Paul
Abstract : INTRODUCTION: Current mouse models of familial brain arteriovenous malformations (AVMs) have limitations in long-term survival. These drawbacks are mainly attributed to systemic and ubiquitous genetic recombinations with development of AVMs in peripheral organs that result in hemorrhagic conditions. METHODS: Transgenic mice with ubiquitous CreER expression were used (ROSA26CreER;Alk1f/f; Alk1-iKO). 4-hydroxytamoxifen (4-OHTM) was stereotactically delivered into the striatum, parietal cortex, or cerebellum of neonatal mice at postnatal day 1. Mice were evaluated for brain AVMs with systemic latex dye perfusion and 3D time-of-flight magnetic resonance angiography. RESULTS: Alk1-iKO mice injected stereotactically with 4-OHTM developed brain AVMs with 68% (21/31) frequency in the striatum, 72% (13/18) in the parietal cortex, and 44% (4/9) in the cerebellum. Brain AVMs formed in or near the injection site with 95% accuracy (36/38). A subset of mice (8%, [3/38]) presented with a communicating hydrocephalus from CSF malabsorption. The formation of AVMs in these Alk1-iKO mice was restricted to the brain, without AVMs developing in peripheral organs (n = 38). The hemoglobin levels were not significantly different between mutant and control Alk1-iKO mice after stereotactic, intracerebral 4-OHTM injection (p = 0.27). The 4-week mortality was 5% (2/38). Longitudinally monitored mice demonstrated good survival at 3 months of age (86%, [6/7]). CONCLUSIONS: We present the first experimental mouse model with local, CreER-mediated induction of brain AVMs. The model is advantageous in generating brain AVMs with high efficiency, along with an improved long-term survival and reduced early lethality of mice. Collectively, these features may serve as a framework to accelerate the ongoing investigations of brain AVM pathogenesis, rupture, and preclinical testing of novel therapeutics.